Changes in Farming Systems and Livelihood Patterns in Mountainous Region of Mizoram, Eastern Extension of the Himalaya - Sati, Vishwambhar Prasad (Indian Journal of Hill Farming, 2016)
This paper looks into the changes in farming systems and livelihood patterns in mountainous regions of Mizoram. Livelihood of the people depends on agriculture and its allied practices. We selected total five villages to conduct this study. Out of the total households (614) in the five villages, 20% households (125) were surveyed randomly. This study was conducted in August 2015. Two time series data (2004 and 2014) on changes in land-use, cropping pattern, livestock, occupation and income and fuel consumption were gathered. Changes in farming systems and livelihood patterns were experienced. Forest and barren land increased by 23.2% and 2%, respectively while, arable land decreased both under shifting and permanent agriculture. In terms of area of crops, cereals and cash crops increased under permanent agriculture whereas, rice, vegetables and orange under shifting cultivation decreased. At the meantime, production and yields of banana, lemon and ginger crops increased. A number of hens (879.8%) and cattle (157.2%) increased and pigs decreased (17.3%). Income from shifting cultivation decreased by 22.7% while, it increased by 92.9% from government services. Simultaneously, a number of people involved in shifting cultivation decreased by 17.5% and their involvement in governmental services and livestock farming increased. Fuel consumption from fuel-wood decreased by 38.2% whereas LPG consumption increased by 30.6%. While responding to the questions, the respondents (672) informed that the changes in farming systems and livelihood patterns are due to high education level, modernization and climate change.